2020
DOI: 10.1002/cncr.32902
|View full text |Cite
|
Sign up to set email alerts
|

Negative affect and stress‐related brain metabolism in patients with metastatic breast cancer

Abstract: Background Cancer and its treatment represent major stressors requiring that patients make multiple adaptations. Despite evidence that poor adaptation to stressors is associated with more distress and negative affect (NA), neuroimmune dysregulation and poorer health outcomes, current understanding is very limited of how NA covaries with central nervous system changes to account for these associations. Methods NA was correlated with brain metabolic activity using 18F‐fluorodeoxyglucose positron emission tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Symptom reduction in anxiety and depression is attributed to the strengthening of the more reflective, top-down cognitive control through increased activation of these brain regions (Clark & Beck, 2010 ). We thus hypothesize that lower activity of these brain regions such as lPFC, vmPFC, Ins, Hy and Th, which we previously found correlated with emotional distress in mBCa patients (13), may be reversed in persons with greater stress management skills for reducing negative mood and distress (Antoni & Dhabhar, 2019 ; Reis et al, 2020a , 2020b ). In other words, we hypothesize here that individual differences in PSMS efficacy are linked to upregulated metabolic activity in similar distress-related brain regions in women with mBC.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Symptom reduction in anxiety and depression is attributed to the strengthening of the more reflective, top-down cognitive control through increased activation of these brain regions (Clark & Beck, 2010 ). We thus hypothesize that lower activity of these brain regions such as lPFC, vmPFC, Ins, Hy and Th, which we previously found correlated with emotional distress in mBCa patients (13), may be reversed in persons with greater stress management skills for reducing negative mood and distress (Antoni & Dhabhar, 2019 ; Reis et al, 2020a , 2020b ). In other words, we hypothesize here that individual differences in PSMS efficacy are linked to upregulated metabolic activity in similar distress-related brain regions in women with mBC.…”
Section: Introductionmentioning
confidence: 80%
“…We provide evidence that higher reported perceptions of stress management skill (PSMS) efficacy relate significantly to more metabolic activity in the insula, thalamus, ventromedial and lateral prefrontal cortices, and basal ganglia. Of all these regions, the insula, thalamus, ventromedial and lateral prefrontal cortices regions have previously shown to show less activation in mBC patients reporting greater emotional distress (Reis et al, 2020a , 2020b ). Further analysis indicated that the association of PSMS with a priori ROIs were mostly specific to the cognitive coping subdomain of PSMS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data of this study is part of a larger study (Travado et al, 2021) in which we examined the association of distress with brain metabolism in women with metastatic breast cancer. We found significantly negative correlations between distress and the activity of the insula, thalamus, hypothalamus, ventromedial prefrontal cortex and lateral prefrontal cortex, which represent key areas necessary for successful adaptation to stressors (Reis et al, 2020). The underactivity of these key brain regions associated with greater distress may contribute to dysregulation of the HPA axis and of cortisol basal diurnal rhythm.…”
Section: Discussionmentioning
confidence: 99%